Get programming learn to code with Python - Bell, Ana (Manning, 2018)
"Learn to code with Python introduces you to the world of writing computer programs without drowning you in confusing jargon or theory that make getting started harder than it should be. Filled with practical examples and step-by-step lessons using the easy-on-the-brain Python language, this book will get you programming in no time! Purchase of the print book includes a free eBook in PDF, Kindle, and ePub formats from Manning Publications. About the Technology: Let's face it. The only way to learn computer programming is to do it. Whether you want to skill up for your next job interview or just get a few pet projects done, programming can be an amazing tool. This book is designed especially for beginners, helping them learn to program hands on, step by step, project by project. It's time to get programming! About the Book: Get Programming: Learn to code with Python teaches you the basics of computer programming using the Python language. In this exercise-driven book, you'll be doing something on nearly every page as you work through 38 compact lessons and 7 engaging capstone projects. By exploring the crystal-clear illustrations, exercises that check your understanding as you go, and tips for what to try next, you'll start thinking like a programmer in no time. What's Inside: Programming skills you can use in any language ... Learn to code-no experience required ... Learn Python, the language for beginners ... Dozens of exercises and examples help you learn by doing. About the Reader: No prior programming experience needed." ... ONIX annotation